Moving away from one disease at a time: Screening, trial design, and regulatory implications of novel platform technologies. Issue 1 (4th February 2023) - Lekstrom‐Himes, Julie; Brooks, P J; Koeberl, Dwight D.; Brower, Amy; Goldenberg, Aaron; Green, Robert C.; Morris, Jill A.; Orsini, Joseph J.; Yu, Timothy W.; Augustine, Erika F.
Abstract: Most rare diseases are caused by single‐gene mutations, and as such, lend themselves to a host of new gene‐targeted therapies and technologies including antisense oligonucleotides, phosphomorpholinos, small interfering RNAs, and a variety of gene delivery and gene editing systems. Early successes are encouraging, however, given the substantial number of distinct rare diseases, the ability to scale these successes will be unsustainable without new development efficiencies. Herein, we discuss the need for genomic newborn screening to match pace with the growing development of targeted therapeutics and ability to rapidly develop individualized therapies for rare variants. We offer approaches to move beyond conventional "one disease at a time" preclinical and clinical drug development and discuss planned regulatory innovations that are necessary to speed therapy delivery to individuals in need. These proposals leverage the shared properties of platform classes of therapeutics and innovative trial designs including master and platform protocols to better serve patients and accelerate drug development. Ultimately, there are risks to these novel approaches; however, we believe that close partnership and transparency between health authorities, patients, researchers, and drug developers present the path forward to overcome these challenges and deliver on the promise of gene‐targeted therapies for rare diseases.